The role of iron metabolism in the pathogenesis and treatment of multiple sclerosis - Duarte-Silva, Eduardo; Meuth, Sven G.; Peixoto, Christina Alves (Frontiers in Immunology, 2023)
Multiple sclerosis is a severe demyelinating disease mediated by cells of the innate and adaptive immune system, especially pathogenic T lymphocytes that produce the pro-inflammatory cytokine granulocyte-macrophage colony stimulating factor (GM-CSF). Although the factors and molecules that drive the genesis of these cells are not completely known, some were discovered and shown to promote the development of such cells, such as dietary factors. In this regard, iron, the most abundant chemical element on Earth, has been implicated in the development of pathogenic T lymphocytes and in MS development via its effects on neurons and glia. Therefore, the aim of this paper is to revise the state-of-art regarding the role of iron metabolism in cells of key importance to MS pathophysiology, such as pathogenic CD4+ T cells and CNS resident cells. Harnessing the knowledge of iron metabolism may aid in the discovery of new molecular targets and in the development of new drugs that tackle MS and other diseases that share similar pathophysiology